Clinical and volumetric changes with increasing functional impairment in familial frontotemporal lobar degeneration. Issue 1 (6th January 2020) - Olney, Nicholas T.; Ong, Elise; Goh, Sheng‐Yang M.; Bajorek, Lynn; Dever, Reilly; Staffaroni, Adam M.; Cobigo, Yann; Bock, Meredith; Chiang, Kevin; Ljubenkov, Peter; Kornak, John; Heuer, Hilary W.; et al.
Abstract: Introduction: The Advancing Research and Treatment in Frontotemporal Lobar Degeneration and Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects longitudinal studies were designed to describe the natural history of familial‐frontotemporal lobar degeneration due to autosomal dominant mutations. Methods: We examined cognitive performance, behavioral ratings, and brain volumes from the first time point in 320 MAPT, GRN, and C9orf72 family members, including 102 non–mutation carriers, 103 asymptomatic carriers, 43 mildly/questionably symptomatic carriers, and 72 carriers with dementia. Results: Asymptomatic carriers showed similar scores on all clinical measures compared with noncarriers but reduced frontal and temporal volumes. Those with mild/questionable impairment showed decreased verbal recall, fluency, and Trail Making Test performance and impaired mood and self‐monitoring. Dementia was associated with impairment in all measures. All MAPT carriers with dementia showed temporal atrophy, but otherwise, there was no single cognitive test or brain region that was abnormal in all subjects. Discussion: Imaging changes appear to precede clinical changes in familial‐frontotemporal lobar degeneration, but specific early clinical and imaging changes vary across individuals.